1990
DOI: 10.1002/art.1780330107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative microfocal radiographic assessment of progression in osteoarthritis of the hand

Abstract: We studied 32 patients with osteoarthritis who had 5x macroradiographs taken of their wrists and hands at 6-month intervals over an 18-month period. The higher magnification and resolution of microfocal radiography permitted the quantitative detection of progressive changes in 4 different features: subchondral sclerosis, the number and size of osteophytes, juxtaarticular radiolucencies, and joint space narrowing. Compared with normal control subjects, subchondral cortical thickness was greater in all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…Using quantitative microfocal radiography, Buck-land-Wright et al [19,20] showed that the changes in OA joints also involve thickening of the sub-chondral cortical plate. In the ACL dog model of OA, Brandt et al [6] reported that, at a later stage of the disease, 54 months after OA induction, there was a marked increase in the volume of subchondral bone with active bone formation.…”
Section: Correlation Between In Vivo Findings In Animals and Human Oamentioning
confidence: 99%
“…Using quantitative microfocal radiography, Buck-land-Wright et al [19,20] showed that the changes in OA joints also involve thickening of the sub-chondral cortical plate. In the ACL dog model of OA, Brandt et al [6] reported that, at a later stage of the disease, 54 months after OA induction, there was a marked increase in the volume of subchondral bone with active bone formation.…”
Section: Correlation Between In Vivo Findings In Animals and Human Oamentioning
confidence: 99%
“…These studies have shown that bony features appear before cartilage narrowing and loss measured radiographically as joint space narrowing 1517 18 …”
mentioning
confidence: 99%
“…1987). In the much smaller joints of the wrist and hand of our patients, no such correspondence was found despite the presence of sclerosis and its change during the study period (Buckland-Wright et al 1990). As the subchondral bone in these joints is narrow, the uptake of bone-seeking isotope would appear to fall below that required for detection by the gamma camera.…”
Section: Discussionmentioning
confidence: 93%
“…The advantages of high spatial resolution and magnification characteristic of this technique (Buckland-Wright 1989) provided detailed images of structures approximating to that of histology (BucklandWright and Bradshaw 1989). Accurate measurement of the dimensions of X-radiographic features can be obtained (Buckland-Wright et al 1986), giving details of the extent (Buckland-Wright and Walker 1987) and progression , 1990) of a disease process. Measurements from the bone scan images were compared with those of the macroradiographic appearance of the X-radiographic features at both baseline and 1 year later.…”
Section: Introductionmentioning
confidence: 99%